Controlling Ministerial Discretion in the Designation of State General Reserve Land Utilization Under Government Regulation No. 20 of 2021 - Muslim Lobubun (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2023)
Government Regulation No. 20 of 2021 establishes State General Reserve Land (TCUN) from abandoned land. Under Articles 27–28 juncto Articles 74 and 87 of ATR/BPN Ministerial Regulation No. 20 of 2021, the Minister holds discretionary authority to determine TCUN allocation. However, broad discretion risks arbitrary land distribution. This study analyzes the legal limits of ministerial discretion in TCUN utilization post-Job Creation Law and formulates control parameters using normative legal research. The study reveals that discretion cannot operate autonomously; it must align with Good Governance Principles (AUPB), the social function of land under Article 6 of the Basic Agrarian Law (UUPA), and agrarian reform goals. This paper proposes a five-stage control model: authority review, discretionary purposes and social function review, agrarian reform relevance review, objectivity and due-care review, and procedural accountability review. Agrarian reform serves as a mandatory consideration whenever TCUN characteristics relate to land redistribution.